2006
DOI: 10.1074/jbc.m513459200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the V Domain of Human Nectin-like Molecule-1/Syncam3/Tsll1/Igsf4b, a Neural Tissue-specific Immunoglobulin-like Cell-Cell Adhesion Molecule

Abstract: Nectins are Ca2؉ -independent immunoglobulin (Ig) superfamily proteins that participate in the organization of epithelial and endothelial junctions. Nectins have three Ig-like domains in the extracellular region, and the first one is essential in cell-cell adhesion and plays a central role in the interaction with the envelope glycoprotein D of several viruses. Five Nectin-like molecules (Necl-1 through -5) with similar domain structures to those of Nectins have been identified. Necl-1 is specifically expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 39 publications
(47 reference statements)
3
47
2
Order By: Relevance
“…Narita et al 21 argued in their model of diff erential dimer formats for cishomodimer and trans -homodimer of nectin-1 that the perpendicular interaction (almost 90 ° between the two molecules) of nectin-1 dimer can only assist cis -interaction (on the same cell surface) because there is not enough angles for two cells to interact in their trans -dimer. Th is notion is indirectly supported by a dimeric structure of Necl-1 in that the two molecules formed a more open angle (approximately 110 ° ) 35 , which is believed to represent a trans -dimer of the family. Th e two crystal structures (free and complex) of the three Ig domains of nectin-1 in our study and the earlier reported structure 21 show that the hinge region between the second Ig-like domain and the third Iglike domain of nectin-1 has some fl exibility, unlike the hinge between the domains 1 and 2.…”
Section: Discussionmentioning
confidence: 77%
“…Narita et al 21 argued in their model of diff erential dimer formats for cishomodimer and trans -homodimer of nectin-1 that the perpendicular interaction (almost 90 ° between the two molecules) of nectin-1 dimer can only assist cis -interaction (on the same cell surface) because there is not enough angles for two cells to interact in their trans -dimer. Th is notion is indirectly supported by a dimeric structure of Necl-1 in that the two molecules formed a more open angle (approximately 110 ° ) 35 , which is believed to represent a trans -dimer of the family. Th e two crystal structures (free and complex) of the three Ig domains of nectin-1 in our study and the earlier reported structure 21 show that the hinge region between the second Ig-like domain and the third Iglike domain of nectin-1 has some fl exibility, unlike the hinge between the domains 1 and 2.…”
Section: Discussionmentioning
confidence: 77%
“…The structures of nectin-1 (three Ig domains) (54), Necl-1 (V domain alone) (36), and Necl-3 (V domain alone) (38) reveal that these molecules also form dimers through the interaction of their V domains. By superimposing nectin-2 on nectin-1, we found that the overall conformation of the dimer formed by nectin-2v is similar to nectin-1, with the root mean square deviation (RMSD) of 1.472 Å (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only three homodimers (three Ig domains of nectin-1, one Ig domain of Necl-1 and Necl-3) and one monomer (two Ig domains of Necl-5) of nine members of this family have been described but with different conclusions (36,38,54,55). The structure of nectin-1 is regarded as a cis-dimer, but Necl-1 is considered a trans-dimer (36,38,54). There is no structural report of any heterodimers for these family members.…”
Section: Discussionmentioning
confidence: 99%
“…Several high-affinity homophilic trans-interactions have been described in detail for nectins/Necls and similar molecules (8)(9)(10)(11)(12)(13). However, the structure and function of the presumably weaker lateral homophilic cis-dimers in cell adhesion and their role in intracellular signaling is not known.…”
mentioning
confidence: 99%
“…Nectins and Necls can function as both ligands and receptors and therefore are able to signal bidirectionally into juxtaposed cells (3,6). To mediate the formation of cell adherens junctions, a model suggests that the extracellular domains of these molecules form ligand-dependent homo-or heterodimers in trans (between molecules located on the same or opposite cell surfaces, respectively) and lateral homodimers in cis, creating a tight network of nectin zippers between juxtaposed cells (7,8). To date, structural and functional studies suggest a mechanism whereby the cis-homodimerization of a receptor on the same cell surface is followed by the formation of a trans-dimer between juxtaposed cells using identical protein interfaces.…”
mentioning
confidence: 99%